1994
DOI: 10.1111/j.1365-2249.1994.tb06604.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA associations with inclusion body myositis

Abstract: SUMMARYInclusion body myositis (IBM) is defined clinically by a characteristic pattern of progressive proximal and distal limb muscle weakness and resistance to steroid therapy, and histologically by the presence of distinctive rimmed vacuoles and filamentous inclusions as well as a mononuclear infiltrate in which CD8"^ T cells are predominant. Muscle damage is believed to be mediated by autoimmune mechanisms, but very little information is available on the immunogenic features of IBM. MHC class I and DR antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 27 publications
3
17
0
1
Order By: Relevance
“…This association has been confirmed in a number of studies in different populations (Love et al, 1991;Garlepp et al, 1994;Koffman et al, 1998;Lampe et al, 2003;Badrising et al, 2004;Price et al, 2004;O'Hanlon et al, 2005;Needham et al, 2008). In addition, in a previous study of HLA serotypes we found that individuals with the HLA-DR3/DR1 combination have a higher disease risk as well as an earlier age-of-onset and more severe weakness (Mastaglia et al, 2009).…”
Section: Introductionsupporting
confidence: 79%
“…This association has been confirmed in a number of studies in different populations (Love et al, 1991;Garlepp et al, 1994;Koffman et al, 1998;Lampe et al, 2003;Badrising et al, 2004;Price et al, 2004;O'Hanlon et al, 2005;Needham et al, 2008). In addition, in a previous study of HLA serotypes we found that individuals with the HLA-DR3/DR1 combination have a higher disease risk as well as an earlier age-of-onset and more severe weakness (Mastaglia et al, 2009).…”
Section: Introductionsupporting
confidence: 79%
“…Whether the frequency of organ-specific and non-organ-specific MAA and MSA is increased in a West Australian s-IBM patient cohort when compared with an ethnically matched population control group; 2. If there is any correlation between AAb and carriage of HLA-DRB1*0301 which encodes HLA-DR3 and is an important risk factor and genetic biomarker for s-IBM (Garlepp et al, 1994;Koffman et al, 1998;Lampe et al, 2003;Badrising et al, 2004;Mastaglia, 2009). As a number of previous studies have compared the relative frequencies of AAb in s-IBM and other inflammatory myopathies this was not addressed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 8.1 ancestral haplotype (HLA A1, B8, DRB3*0101, DRB1*0301, DQB1*0201) predisposes to many autoimmune diseases and has been strongly linked with IBM [10][11][12], PM and DM [13].…”
Section: Introductionmentioning
confidence: 99%